Piosenki Jacka Kaczmarskiego w aspekcie zagadnienia melosemii - Dźwinel, Kamil (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article presents the phenomenon named by the author melosemy. Melosemy is a sensible additions of the poetic text by the connection of his semantic structures with the melody or with vocal and instrumental techniques. The exemplary material for the presentation of this phenomenon from the borderline of music and text are songs of a contemporary polish poet singing own texts with the accompaniment of a guitar — Jacek Kaczmarski (1957—2004). Melosemy is treated as an important aesthetic category in the creativeness of the bard. The conclusion of the text opens a wider research area: it is possible to find melosemy both in the creative output of other authors from the range of the poetic song, as well as in soundtracks and folk music.